2016
DOI: 10.1093/ehjci/jev301
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mitral annulus function and mitral regurgitation severity and left atrial remodelling in patients with primary mitral regurgitation

Abstract: In patients with OMR, MA reduced function correlates with the MR severity and the LA size and function, but not with the LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
20
1
1
Order By: Relevance
“…Prior studies have presented a broad range of normal MA dimensions. 3D echocardiographic studies have reported normal mid-systolic values ranging from 8.2 to 10.5 cm 2 for 3D area, 106 to 128 mm for perimeter, 28 to 32.7 mm for AP diameter, 38.7 to 39 mm for IC diameter, and 6.6 to 7.9 mm for height 11 13 . Similar results have been conducted on CT, with one study reporting a mean MA area of 8.9 ± 1.5 cm 2 , perimeter of 110 ± 9 mm, AP diameter of 27.5 ± 2.7 mm and IC diameter of 37.6 ± 3.7 mm 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have presented a broad range of normal MA dimensions. 3D echocardiographic studies have reported normal mid-systolic values ranging from 8.2 to 10.5 cm 2 for 3D area, 106 to 128 mm for perimeter, 28 to 32.7 mm for AP diameter, 38.7 to 39 mm for IC diameter, and 6.6 to 7.9 mm for height 11 13 . Similar results have been conducted on CT, with one study reporting a mean MA area of 8.9 ± 1.5 cm 2 , perimeter of 110 ± 9 mm, AP diameter of 27.5 ± 2.7 mm and IC diameter of 37.6 ± 3.7 mm 10 .…”
Section: Discussionmentioning
confidence: 99%
“…MA motion serves as an important clinical indicator of regional as well as global LV function 7 . Previous attempts to assess the MA dynamics and geometry include using 2D or 3D echocardiography and computed tomography (CT) 8 13 . These approaches suffer from either limited spatial resolution and coverage 8 , 14 , 15 or ionizing radiation 9 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, annulus height is close to normal. Annular enlargement is correlated with severity of MR (27,28). Importantly, annular enlargement in patients with MD is different from that of patients with ischemic MR, in which only the anteroposterior annulus is enlarged.…”
Section: Mitral Annulus Dynamicsmentioning
confidence: 99%
“…Inconsistent data on annular measurements in the literature may be related to which anatomic landmarks are assessed. [5][6][7][8][9][10][16][17][18] One example is the distance between the commissures, for which a number of approaches have been reported in the literature: intercommissural width, extended CW, commissure to commissure, maximum transverse diameter, longest diameter, and anterolateralposteromedial diameter. Therefore, estimations of annular area and AHCWR may depend on which anatomic landmarks were included in the measurements.…”
Section: Measuring Mitral Annular Dynamicsmentioning
confidence: 99%
“…Furthermore, different definitions of the NPA most probably explain the wide range of systolic NPA values reported in healthy control subjects (ranging from 127 to 147 ). Different ''nadir points'' are chosen, including the lowest coaptation point, 6,[16][17][18] as was demonstrated by the fact that MPR was associated with less saddle shape or, alternatively at the level of the commissures (3D VSAS), with a higher degree of nonplanarity. Figure 8 illustrates the difference in how these measurements are obtained.…”
Section: Measuring Mitral Annular Dynamicsmentioning
confidence: 99%